2019
DOI: 10.3390/jcm8040498
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Operating Conditions, Postoperative Pain and Recovery, and Overall Satisfaction of Surgeons with Deep vs. No Neuromuscular Blockade for Spinal Surgery under General Anesthesia: A Prospective Randomized Controlled Trial

Abstract: We aimed to investigate operating conditions, postoperative pain, and overall satisfaction of surgeons using deep neuromuscular blockade (NMB) vs. no NMB in patients undergoing lumbar spinal surgery under general anesthesia. Eighty-three patients undergoing lumbar fusion were randomly assigned to receive deep NMB (n = 43) or no NMB (n = 40). In the deep-NMB group, rocuronium was administered to maintain deep NMB (train-of-four count 0, post-tetanic count 1–2) until the end of surgery. In the no-NMB group, suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…Despite maintaining the BIS within 40-60, the average propofol infusion rate in group A was higher than that in group T, which was consistent with previous results 16 . The reason for this result is unclear, although it is likely due to the shallower NMB in group A, which falsely elevating the BIS values of the patients through higher electromyographic activity, resulting in a higher infused dose of propofol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite maintaining the BIS within 40-60, the average propofol infusion rate in group A was higher than that in group T, which was consistent with previous results 16 . The reason for this result is unclear, although it is likely due to the shallower NMB in group A, which falsely elevating the BIS values of the patients through higher electromyographic activity, resulting in a higher infused dose of propofol.…”
Section: Discussionsupporting
confidence: 91%
“…These ndings may extend to lumbar surgery because relaxed lumbar spine muscles could provide better surgical conditions. Recently, a study investigating surgical conditions of lumbar surgery presented that deep NMB provided better surgical conditions with lower lumbar retractor pressure and higher overall satisfaction score evaluated by surgeons than no NMB 16 . We observed outcomes that were consistent with those reported previously; compared with group A, in the group T, which manifested deeper NMB, the overall surgical satisfaction score evaluated by the surgeon was superior, and the lumbar muscle tone and lumbar retractor pressure were lower, which resulted in better surgical conditions in group T. Hence, the acceleromyography at the trapezius could more accurately re ect the actual NMB values in the lumbar spine muscles than that of the adductor pollicis muscle.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated the effect of NMB on intraoperative and postoperative outcomes during spinal surgery 2,3 . They mainly evaluated surgical conditions and recovery profiles according to the depth of NMB, but did not address postoperative sore throat and hoarseness.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromuscular blocking agents are routinely used to facilitate tracheal intubation during induction of anesthesia and are commonly used to improve surgical conditions during the maintenance of general anesthesia. However, there have also been several concerns about their effectiveness in improving surgical conditions and side effects, including delayed recovery, residual paralysis, and hypersensitivity reactions [1][2][3][4] .…”
mentioning
confidence: 99%
“…However, studies on post-surgical outcomes are recent. Oh et al [ 92 ] reported that deep NMB not only improved the surgical condition but also reduced postoperative pain in lumbar spinal surgery. Mulier and Dillemans [ 93 ] revealed that continuous deep NMB is an independent factor associated with fewer complications after bariatric surgery.…”
Section: Recent Clinical Interests Regarding Sugammadexmentioning
confidence: 99%